2021
DOI: 10.1017/s1355617721000795
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Outcome after Mild Traumatic Brain Injury in Older People

Abstract: Objective: Older age is often identified as a risk factor for poor outcome from traumatic brain injury (TBI). However, this relates predominantly to mortality following moderate–severe TBI. It remains unclear whether increasing age exerts risk on the expected recovery from mild TBI (mTBI). In this systematic review of mTBI in older age (60+ years), a focus was to identify outcome through several domains – cognition, psychological health, and life participation. Methods: Fourteen studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 85 publications
1
23
0
1
Order By: Relevance
“…In CENTER-TBI, older adults do not seem to have higher proportions of depression and anxiety than TBI adults in general [49] . This is consistent to previous studies, which found that older adults report less psychological distress than younger adults [14] . However, the proportion of patients with severe depression and anxiety symptoms is higher than in the general population without TBI [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In CENTER-TBI, older adults do not seem to have higher proportions of depression and anxiety than TBI adults in general [49] . This is consistent to previous studies, which found that older adults report less psychological distress than younger adults [14] . However, the proportion of patients with severe depression and anxiety symptoms is higher than in the general population without TBI [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Research on outcome following TBI in older adults has predominantly focused on subgroups of TBI severity and functional outcome [14] . In CENTER-TBI, we found that age and injury characteristics were associated with lower functional outcome but were not significant predictors of mental HRQoL and psychological symptoms when controlled for other important factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations